AquaLink in HAB detection: integrating IoT and 3D-printed PETG for monitoring aquaculture conditions conducive to HAB - Nik Mohd Kamal, Nik Nor Muhammad Saifudin; Zainuddin, Ahmad Anwar; Amir Hussin, Amir 'Aatieff; Mohammad Noor, Normawaty; Mohd Razali, Roziawati; Ayub, Mohd Nor Azman; Harman, Muhammad Farouk (ECTI Association Sirindhon International Institute of Technology, 2025)
Harmful algal blooms (HABs) pose a serious threat to aquaculture and environmental health, often resulting in considerable ecological and economic impacts. Conventional water quality monitoring techniques, often manual and time-consuming, are inadequate for the timely detection of conditions that promote HAB formation. To overcome these limitations, the AquaLink system was developed by integrating the Internet of Things (IoT) technology with 3D-printed polyethylene terephthalate glycol (PETG) enclosures, enabling scalable, real-time, and cost-eective monitoring of water quality. The system employs sensors to measure essential parameters, including atmospheric pressure, temperature, and turbidity, with data transferred through Raspberry Pi and ESP32 controllers to an IoT dashboard for real-time analysis and visualisation. PETG-based casings were combined with IoT-enabled sensors to improve durability and reduce biofouling in aquatic environments. Prototypes were tested across dierent water bodies to validate performance under real-world conditions. The results demonstrated that the system eectively provided real-time monitoring of aquaculture environments, allowing the early identication of HAB risks through continuous tracking of water quality indicators. Beyond its technical contributions, AquaLink oers societal benets by serving as a low-cost, ecient tool that reduces sh mortality, limits environmental degradation, and enhances food security. The exibility and scalability of the system make it applicable to small-scale and industrial aquaculture operations, fostering sustainable practices through advanced environmental monitoring.